2018
DOI: 10.1002/cti2.1014
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation of the unfolded protein response at the mucosal barrier in viral infection

Abstract: Protein folding in the endoplasmic reticulum (ER) is subject to stringent quality control. When protein secretion demand exceeds the protein folding capacity of the ER, the unfolded protein response (UPR) is triggered as a consequence of ER stress. Due to the secretory function of epithelial cells, UPR plays an important role in maintaining epithelial barrier function at mucosal sites. ER stress and activation of the UPR are natural mechanisms by which mucosal epithelial cells combat viral infections. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…In many viral infections, viruses commandeer vital cellular components, leading to cellular stress. Cellular stress is often represented as unfolded protein response (UPR) in cells (Geller et al, 2012; Wang et al, 2018). Previous studies have reported that ORF3 and ORF2 of the virus induce UPR and ER stress (Surjit et al, 2007; John et al, 2011; Xu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In many viral infections, viruses commandeer vital cellular components, leading to cellular stress. Cellular stress is often represented as unfolded protein response (UPR) in cells (Geller et al, 2012; Wang et al, 2018). Previous studies have reported that ORF3 and ORF2 of the virus induce UPR and ER stress (Surjit et al, 2007; John et al, 2011; Xu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Ca 2+ flux also facilitates the induction of ER stress during CVB infection ( 40 , 62 66 ). While ironclad proof of direct causality has remained elusive, CVB infection is highly associated with T1D onset in humans ( 67 75 ). Furthermore, a number of studies have defined footprints of CVB infection in the islets, demonstrated through the presence of RNA and VP1 antibody staining ( 70 , 74 , 76 80 ).…”
Section: Er Stress In β Cells Is Influenced By Immunologic and Enviromentioning
confidence: 99%
“…Multiple reports in the past have shed light on the cell's UPR pathway to ER stress and have shown that these three legs of UPR when functioning properly can lead to either the alleviation of stress and, hence, survival of the cell or stimulation of apoptosis pathways that lead to cell death (3,(9)(10)(11). These checks and balances not only ensure healthy maintenance of the cell but also protect a colony of cells from external infections (1,9,12,13).…”
Section: Introductionmentioning
confidence: 99%